Effects of different exercise types on visceral fat in young individuals with obesity aged 6–24 years old: A systematic review and meta-analysis - Wang, Rong; Zhang, Xiaoyuan; Ren, Hong; Zhou, Huixuan; Yuan, Yaqing; Chai, Yunlong; Hou, Xiao (Frontiers in Physiology, 2022)
Introduction: The prevalence of pediatric obesity remains high all over the world. Various exercise interventions have been applied to decrease the visceral fat in young individuals with obesity. But the evidence remains controversial on the effect of the exercise on visceral fat. Moreover, it is unclear which type of the exercise is the most effective for young individuals with overweight or obesity to reduce visceral fat. Objective: The objective of this review and meta-analysis is to evaluate and compare the effectiveness of different exercise interventions on visceral fat in young individuals with overweight or obesity. Methods: Four databases consisting of PubMed, Web of Science, EBSCO, and Cochrane Library were searched prior to May 2022. Fifteen studies with a total of 30 data points involving 1,134 participants were included in this meta-analysis. And the interventions were limited to 4 exercise types [i.e., aerobic exercise (AE), resistance exercise (RE), aerobic exercise combined with resistance exercise (CE), and high-intensity interval training (HIIT)]. Data Synthesis: The results showed that AE (Standardized Mean Difference = −0.32; 95% CI = −0.50 to −0.13; p = 0.0007; I2 = 37%) and HIIT (SMD = −0.59; 95% CI = −0.87 to −0.31; p < 0.0001; I2 = 0%) had a significant reduction effect on visceral fat. And the effect of HIIT seemed better than AE. However, RE (SMD = −0.58; 95% CI = −1.34 to 0.17; p = 0.13; I2 = 76%) and CE (SMD = −0.21; 95% CI = −0.81 to 0.38; p = 0.48; I2 = 63%) had a non-significant effect on visceral fat decline. Additionally, compared with the control group, exercise interventions had a significant effect on reducing visceral fat in adolescents (SMD = −0.54; 95% CI = −0.82 to −0.26; p = 0.0001; I2 = 64%) and young adults (SMD = −0.42; 95% CI = −0.69 to −0.15; p = 0.003; I2 = 0%) rather than children (SMD = −0.15; 95% CI = −0.32 to 0.02; p = 0.08; I2 = 0%). And the gender-based subgroup analysis indicated that the effectiveness of the exercise on the reduction of visceral fat was more significant in males (SMD = −1.27; 95% CI = −1.67 to −0.87; p < 0.00001; I2 = 0%) than that in females (SMD = −0.31; 95% CI = −0.48 to −0.14; p = 0.0004; I2 = 0%). Conclusion: This review and meta-analysis demonstrates that exercise interventions are efficient to decrease visceral fat in adolescents (12–18 years old) and young adults (18–24 years old). Among different exercise types, AE and HIIT are helpful for young individuals with overweight or obesity to reduce visceral fat and HIIT appears to be the most effective exercise intervention. In addition, the effect of exercise interventions on the consumption of visceral fat is more significant in males than that in females. Systematic Review Registration: [http://www.crd.york.ac.uk/PROSPERO], identifier [CRD42022310878].